Duplication cyst with midgut volvulus in a neonate: an unusual presentation. Issue 8 (26th August 2020) - Pai, Nitin G; Prabhu, Santosh; Prabhakar, Pavithra; Kumar, Vijay
Abstract : Incomplete intestinal fixation or malrotation of gut with midgut volvulus is one of the important causes of bilious vomiting in neonates. The incidence of malrotation of gut in population is 4% and that of duplication cyst is 1:4500. Patients with malrotation are prone to develop midgut volvulus due to their narrow mesenteric base demanding urgent surgical intervention. Common associated anomalies are intrinsic duodenal obstruction, internal hernias, caecal volvulus, anorectal malformations and Hirschsprung's disease. The present case refers to a 4-day-old neonate who presented with malrotation of gut with reverse volvulus and an associated gastrointestinal duplication cyst, which is a rare association with only few reported case reports. After imaging with ultrasound and contrast radiograph, the baby underwent prompt surgical intervention in the form of Ladd's procedure with resection and anastomosis of jejunal duplication cyst.